2014
DOI: 10.1038/ncomms6072
|View full text |Cite
|
Sign up to set email alerts
|

XTACC3–XMAP215 association reveals an asymmetric interaction promoting microtubule elongation

Abstract: chTOG is a conserved microtubule polymerase that catalyses the addition of tubulin dimers to promote microtubule growth. chTOG interacts with TACC3, a member of the transforming acidic coiled-coil (TACC) family. Here we analyse their association using the Xenopus homologues, XTACC3 (TACC3) and XMAP215 (chTOG), dissecting the mechanism by which their interaction promotes microtubule elongation during spindle assembly. Using SAXS, we show that the TACC domain (TD) is an elongated structure that mediates the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(43 citation statements)
references
References 38 publications
4
39
0
Order By: Relevance
“…On the other hand, the C‐terminal binding region of XMAP is predicted to be a coiled‐coil. When isolated, it tends to populate helical structures and a short peptide XMAP‐pCt (Table ), with similar structural propensities was described . It has also been shown that the pCt peptide has a good affinity to TD4 and, for this reason, it is an appropriate model to mimic the intermolecular interactions of the full‐length protein.…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations
“…On the other hand, the C‐terminal binding region of XMAP is predicted to be a coiled‐coil. When isolated, it tends to populate helical structures and a short peptide XMAP‐pCt (Table ), with similar structural propensities was described . It has also been shown that the pCt peptide has a good affinity to TD4 and, for this reason, it is an appropriate model to mimic the intermolecular interactions of the full‐length protein.…”
Section: Introductionmentioning
confidence: 79%
“…Mortuza et al, defined a minimal active binding TACC domain (TD4, 26 kDa) for the protein XTACC3 (the Xenopus homologue of the human TACC3, 81% sequence similarity) as well as that of XMAP215 (Ct, 7kDa). It is well known that human centrosomal proteins show a significant tendency to adopt both unstructured and coiled‐coils conformers which complicates the determination of their structure at atomic resolution.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We and others have previously shown that XTACC3 promotes microtubule assembly at the centrosome in Xenopus egg extracts. Indeed, depletion of XTACC3 results in a significant reduction of microtubules by 40% in the centrosome asters, but it does not impair bipolar spindle formation in cycled egg extracts (Kinoshita et al, 2005;Mortuza et al, 2014;Peset et al, 2005;Sardon et al, 2008). We first incubated Xenopus sperm nuclei carrying one centrosome in mock-(control) or XTACC3-depleted CSF extracts ( Fig.…”
Section: The Kinetics Of Spindle Bipolarization Are Adjustablementioning
confidence: 99%